Pemahaman Guru Pendidikan Agama Islam terhadap Istilah Tarbiyah, Ta‘lim, dan Ta’dib dalam Praktik Pembelajaran - Marzuki, Darlina Nuralisyarifah; Najmi, Lailan; Jamilus, Jamilus (YASIN, 2025)
Although the concepts of tarbiyah, ta‘lim, and ta’dib have been widely discussed in Islamic education studies, research that specifically examines Islamic Religious Education teachers’ understanding of these three concepts and their implications for classroom instructional practice remains relatively limited. This study aimed to explore Islamic Religious Education teachers’ understanding of the terms tarbiyah, ta‘lim, and ta’dib and how this understanding is manifested in their teaching practice. The study employed a qualitative approach with a field study design involving ten Islamic Religious Education teachers selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were then analyzed using thematic analysis. The findings indicate that Islamic Religious Education classroom practice remains dominated by a ta‘lim-oriented approach that focuses on content delivery and cognitive achievement, whereas the concept of tarbiyah is more often understood implicitly as the cultivation of religious attitudes and habits, and ta’dib tends to be reduced to general etiquette or politeness. These results reveal a gap between the normative concepts of Islamic education and pedagogical practice in formal schools and provide an empirical contribution to the development of contemporary Islamic education studies. The study concludes by underscoring the importance of integrating tarbiyah, ta‘lim, and ta’dib holistically within Islamic Religious Education instruction and recommends strengthening teachers’ conceptual competence through continuous professional development programs to improve instructional quality and the formation of adab and student character.